The effect of religiosity and financial literacy on intention to use Islamic banking products - Istyakara Muslichah; Soliha Sanusi (Faculty of Business & Economics, Universitas Islam Indonesia, 2019)
Purpose: Cosiderable numbers of study provides and widen the horizon of knowledge on the intentions of people or business to use religious-related banking product.With the increasing awareness of Islamic banking product, this study aims to probe the relationship between knowledge of Islamic finance and religiousity with the intention of consumer to use Islamic banking products.Methodoloy: Using convenient sampling, this research uses questionnaires to gather primary data from business owners or managers in Yogyakarta as the respondents. SMART PLS is used to analyzed the data.Findings: This result show that business players’ intention to use Islamic banking products is influenced by religiosity, literacy and attitude. Meanwhile, the effect of Islamic financial literacy on the intention to use Islamic banking products shows a greater influence compared to other relationship. Knowledge, especially being financially literate is very important to increase the interest of industry players using Islamic products.Originality/Value: To the author knowledge, as the results variations among researcher exist, the findings of this research provides deeper insight on the literature of behavior and norms as well as Islamic financial literacy. This paper suggests that knowledge and religiousity matters as for business payers to make utilization decision related to Islamic banking product.